Penerapan Pemisahan Kelas Antara Siswa Putra dan Siswa Putri dalam Upaya Pembinaan Akhlak di SMP Muhammadiyah 10 Surakarta - Rahmadani*, Suci; Latifatul Inayati, Nurul (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
Formal education, especially in madrasahs, has an important role in shaping the personality of its students This research was motivated by factors in the application of separate class groupings between male and female students at SMP Muhammadiyah 10 Surakarta, as an effort to foster student morals. Through the implementation of separate classes between male and female students, it is hoped that the school can become a place for the formation of students' character and personality into individuals with charismatic character. The method used is a qualitative approach with field observation, interviews and documentation and it was found that the factors that became the background to the implementation of the separation of male and female classes include internal factors where the teacher is easier to condition the class and more effectively determine learning strategies and methods, and for students able to show activeness in class and confidence in expressing their interests and talents and able to  exercise self-control with separate classes between sons and daughters. While external factors are the influence of globalization that is growing very rapidly and lack of attention from parents / guardians because of their busy lives. But the impact is not good, they tend to be more aggressive outside the madrasa. So that in addition to class separation, sufficient religious knowledge is needed for students. The class separation policy at SMP Muhammadiyah 10 Surakarta is carried out with various considerations, one of which is because currently students and students have entered adolescence, so it is feared that things will happen that are not desirable between fellow students. This is in accordance with the school's vision and mission, which is to create a generation that has the character of akhlakul karimah.